The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/cctc.202200186
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Driven Carboxylation of Olefins by Using 2D Metal‐Free Covalent Organic Framework as Intrinsic Photocatalyst: A Sustainable Approach for CO2 Utilization

Abstract: Photocatalytic metal-free carboxylation of olefins offers an environment-friendly approach for resolving the increasing energy issue as well as mitigating the dilemma caused by the greenhouse effect. Carboxylation of styrene and its derivatives by photocatalytic CO 2 reduction reaction shows great potential for sustainable utilization of greenhouse gas CO 2 into valuable chemicals. Herein, we have constructed a highly crystalline and thermally stable 2D porous covalent organic framework (COF) having very low b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 93 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…The presence of p ‐terphenyl as co‐catalyst and triethanolamine (TEA) as a sacrificial electron donor was necessary ( Scheme ). [ 193 ] The α‐to‐β product ratios are not correlated with the substituents on styrene. For example, the alpha position is more prone to reaction in styrenes including methoxy, nitro, chloro, and cyano groups.…”
Section: Photocatalytic Organic Transformations Mediated By Cofsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of p ‐terphenyl as co‐catalyst and triethanolamine (TEA) as a sacrificial electron donor was necessary ( Scheme ). [ 193 ] The α‐to‐β product ratios are not correlated with the substituents on styrene. For example, the alpha position is more prone to reaction in styrenes including methoxy, nitro, chloro, and cyano groups.…”
Section: Photocatalytic Organic Transformations Mediated By Cofsmentioning
confidence: 99%
“…Finally, the carboxylated product is generated via the protonation of the anion, and the TR‐OT‐COF is regenerated by the sacrificial electron donor TEA. [ 193 ]…”
Section: Photocatalytic Organic Transformations Mediated By Cofsmentioning
confidence: 99%
See 1 more Smart Citation
“…Islam et al 104 reported the construction of a highly crystalline and stable 2D-COF with a very low band gap for the carboxylation of unsaturated olefins with CO 2 . The COFs were synthesised by Schiff base condensation using trimethyl resorcinol and o -toluidine as building blocks.…”
Section: Application Of Metal-free Cof-based Photocatalysts In Enviro...mentioning
confidence: 99%
“…On the contrary, the band gap of organic semiconductors is tuned straightforwardly via the involvement of a wide range of monomeric units. Recently, organic porous materials like conjugated microporous polymers (CMPs), , carbon nitrides, hyper-cross-linked polymers (HCPs), and covalent triazine-based frameworks (CTFs) have been investigated for light-driven reduction of CO 2 . The aforementioned organic materials are generally amorphous in nature; in contrast, COFs can be capable of combining porosity with their crystallinity. Recently, we demonstrated a metal-free crystalline covalent organic framework as a reusable heterogeneous photocatalyst for visible-light-promoted photocatalytic carboxylation of olefins with CO 2 into carboxylic acid . COFs were also selected as photocatalytic systems for water splitting, , and for electrochemical reduction of CO 2 . , These highly ordered crystalline porous polymers also have the potential to be a great asset for direct photoreduction of CO 2 into value-added chemicals: for instance, an azine-functionalized COF, N 3 -COF, was described to promote gas phase selective photoreduction of CO 2 into methanol .…”
Section: Introductionmentioning
confidence: 99%